PERANAN ORGANISASI KEMAHASISWAAN TERHADAP PERKEMBANGAN KETERAMPILAN NON TEKNIS MAHASISWA UNIVERSITAS PENDIDIKAN INDONESIA - Augita Ria Idauli; Elisa Fitri; Supriyono Supriyono (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Student organizations are organizations within the university whose members are students with the aim of accommodating the talents, interests, and potential of students which are carried out outside of lecture activities. So that the objectives of this study are (1) To determine the role of student organizations in the development of soft skills of students at the University of Education of Indonesia. (2) Knowing the types of soft skills that have developed during organizational activities. The method used in this research is a questionnaire method. This research was conducted by distributing questionnaires online with google form media. The subjects in this study were active students of the Department of Chemistry at the University of Education of Indonesia who participated in organizations within the author's environment. The results obtained were (1) student organizations that have a very important role and support the development of soft skills themselves and (2) 88% of students stated that the types of soft skills that have developed are cooperation and collaboration.